2020
DOI: 10.1007/s00259-020-05059-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimal 68Ga-PSMA and 18F-PSMA PET window levelling for gross tumour volume delineation in primary prostate cancer

Abstract: This study proposes optimal tracer-specific threshold-based window levels for PSMA PET-based intraprostatic gross tumour volume (GTV) contouring to reduce interobserver delineation variability.Methods: Nine 68 Ga-PSMA-11 and nine 18 F-PSMA-1007 PET scans including GTV delineations of four expert teams (GTVmanual) and a majority-voted GTV (GTVmajority) were assessed with respect to a registered histopathological GTV (GTVhisto) as gold standard reference. The standard uptake values (SUVs) per voxel were converte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Recent studies have considered the impact of technical considerations such as image scaling on interobserver variability in contouring tasks: Zamboglou et al 25 described significantly greater agreement when uniform SUV windowing of 0-5 (DSC 0.80) was employed (as was used here) compared to nonstandardised scaling methods (DSC 0.56). 25 Draulans et al 26 found alternatively that windowing of 0-41% SUV max optimised the accuracy of contours with reference to histopathology. 26 Similar considerations may apply to bpMRI, where choice of b-values or the incorporation of simulated high b-value DWI could improve consistency between observers on bpMRI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have considered the impact of technical considerations such as image scaling on interobserver variability in contouring tasks: Zamboglou et al 25 described significantly greater agreement when uniform SUV windowing of 0-5 (DSC 0.80) was employed (as was used here) compared to nonstandardised scaling methods (DSC 0.56). 25 Draulans et al 26 found alternatively that windowing of 0-41% SUV max optimised the accuracy of contours with reference to histopathology. 26 Similar considerations may apply to bpMRI, where choice of b-values or the incorporation of simulated high b-value DWI could improve consistency between observers on bpMRI.…”
Section: Discussionmentioning
confidence: 99%
“…25 Draulans et al 26 found alternatively that windowing of 0-41% SUV max optimised the accuracy of contours with reference to histopathology. 26 Similar considerations may apply to bpMRI, where choice of b-values or the incorporation of simulated high b-value DWI could improve consistency between observers on bpMRI. 27 Ultimate optimisation of image scaling and display is likely dependent on specific scanner, image acquisition and patient characteristics, and should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manual Contouring: According to recommendations for [ 68 Ga]-PSMA-PET imaging scaling of SUVmin-max 0-5 was firstly applied for intraprostatic tumor lesion contouring (11). Due to volume overestimation and differences in SUVuptake between both tracers (17,22), a second analysis applying individual scaling was performed to define an additional scaling range for manual contouring, which results in absolute volumes (GTV-Individual) more consistent with GTV-Histo. Therefore, PET images of each patient were scaled individually by modifying the scaling value of the upper SUV-limit, adjusting the volume to the available histological information.…”
Section: Pet Based Contouringmentioning
confidence: 99%
“…Fluorine-18-labeled Tracers ([ 18 F]PSMA-1007) have been implemented in nuclear medicine practice, with suspected benefits due to lesser renal elimination and consequent less background signal in the bladder (15) and performed with good diagnostic accuracy (16). Since [ 68 Ga]-and [ 18 F]PSMA-1007 tracers show differences in SUV distribution scaling recommendations might not be used interchangeable (17). This prospectively designed study aims to validate [ 18 F]PSMA-1007 PET based contouring approaches for intraprostatic tumor contouring using whole mount histopathology as standard of reference, since a consensual method to accurately contour intraprostatic lesions for this tracer has not yet been established.…”
Section: Introductionmentioning
confidence: 99%